DEVELOPMENT OF ANTI CORRUPTION BASED CITIZENSHIP EDUCATION BOOKS AT UNIVERSITY - Inge Angelia; Naufal Raid; Edison Edison (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
The high rate of corruption in the world is a serious problem globally. Indonesia in 2021 based on data from Transparency International Indonesia, the results of the corruption perception index are ranked 96th out of 180 countries. Referring to this phenomenon through Citizenship education, it is necessary to have an anti-corruption-based textbook. This research aims to develop textbooks on Citizenship Education Based on Anti-Corruption in Higher Education that are valid and practical for the course Citizenship Education in Higher Education. The process of developing this textbook refers to the Plomp development model. The results of the study showed that the validity of Anti-Corruption-Based Civics textbooks on the validity criteria was very valid with an average Aiken's v 0.81. The practicality of textbooks is in the practical category with an average of 3.71. Student learning activities with anti-corruption-based Civics textbooks with phases: problem orientation, hypotheses, testing consequences, character exploration, presentations, self-reflection. Based on these results, the Anti-Corruption-Based Civic Education textbook meets valid and practical criteria and is expected to be an alternative reference for improving the quality of civic education learning, especially in anti-corruption education.